A Near-Infrared Light Triggered Composite Nanoplatform for Synergetic Therapy and Multimodal Tumor Imaging - Wu, Mingzhou; He, Shuqing; Hu, Xin; Chen, Jingqin; Ha, Enna; Ai, Fujin; Ji, Tao; Hu, Junqing; Ruan, Shuangchen (Frontiers in Chemistry, 2021)
Transition-metal chalcogenides compound with both facile preparation and multifunctional element are strongly desired to act as ideal photothermal agents for cancer theranostics. Herein, this work synthesize interesting Cu7.2S4/5MoS2 composite nanoflowers and investigate the crystal growth mechanism to optimize the synthesis strategy and obtain excellent photothermal therapy agents. Cu7.2S4/5MoS2 exhibit a high photothermal conversion efficiency of 58.7% and work as a theranostic nanoplatform and demonstrated an effective photothermal-chemodynamic-photodynamic synergetic therapeutic effect both in vitro and in vivo tests. Moreover, Cu7.2S4/5MoS2 show strong photoacoustic signal amplitudes and computed tomographic contrast enhancement in vivo. These inspired results suggest the great potential application of Cu7.2S4/5MoS2 composite nanoflowers as a photo/H2O2-responsive therapeutic-agent against tumors.